PEKERJA DI BAWAH UMUR DALAM KARYA LUKIS REALIS - WINARNO, Drs. Erfahmi, M.Sn., Drs. Abd. Hafiz, M.Pd. (Universitas Negeri Padang, 2017)
The purpose of creating these art work is visualized a issue in society. One of interesting issue is underage worker. All of ideas reated to this issue wil visualized though realist painting, realis painting is kind of art work whach minies all of shape ingnoring subjektiviti. Along the progress of these art works, painter is using oil and canvas as media. The issue of underage works will titles, such as: 1) Firewood seller, 2) Bread seller, 3) A Mechanik, 4) A flat tire repair man, 5) Street meatballs seller, 6) stone potter, 7) Stone bearer, 8) Potter on the harbor, 9) Chart puling man, and 10) Siomay selle.Kata kunci: Pekerja di bawah umur, seni lukis, realis